Kemampuan Baca Tulis Al-Qur’an dan Motivasi Tadarus Al-Qur’an - Siddiq, Hasbi (Al-Riwayah : Jurnal Kependidikan, 2016)
In Surah Al-Alaq: 96/1-5 God mentions the importance of reading in everyday life with his words: “Read the (call) the name of your Lord who created, He created man from a clot. Read, and thy Lord the Most generous, who taught (man) with words intermediately, He teaches man what he did not know “. This means that a reader becomes the springs of human civilization for in their life. Islam greatly appreciates the reading process in the form of whatever reading. Reading means wanting everything that is not yet known. Thus, reading is important so the basic meaning of the Quran is reading. Inculcating the habit of reading to the students needs a great effort, especially al-Quran. The article below explains the motivation of writing and reading the Quran in the the month of Ramadan